2022
DOI: 10.36519/idcm.2022.154
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Assessment of Young Adults Before and After Initiation of Combination Antiretroviral Therapy

Abstract: Objective: In the determination and monitoring of neurocognitive disorders in human immunodeficiency virus (HIV)-positive individuals, there is a need for significantly more practical methods which provide results in a shorter time than the tests that require challenging and specialized expertise. This study aimed to evaluate cognitive functions and the factors affecting them in naïve HIV-positive patients using by Montreal Cognitive Assessment (MoCA) test before and after the initiation of combination antiret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Previous studies utilizing MoCA to examine the relationship be- and after ART and found no relationship between MoCA scores and alcohol or substance use at baseline (Gül et al, 2022). Importantly, and in contrast to the present study, a history of alcohol or substance abuse was an exclusion criterion for study participation, and the study did not mention what alcohol measure was used to assess alcohol consumption.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Previous studies utilizing MoCA to examine the relationship be- and after ART and found no relationship between MoCA scores and alcohol or substance use at baseline (Gül et al, 2022). Importantly, and in contrast to the present study, a history of alcohol or substance abuse was an exclusion criterion for study participation, and the study did not mention what alcohol measure was used to assess alcohol consumption.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies utilizing MoCA to examine the relationship between cognitive function and alcohol use in PWH are limited, and this study is the first to examine this relationship in the NOAH cohort. A recent study from Gül and colleagues examined MoCA scores before and after ART and found no relationship between MoCA scores and alcohol or substance use at baseline (Gül et al., 2022). Importantly, and in contrast to the present study, a history of alcohol or substance abuse was an exclusion criterion for study participation, and the study did not mention what alcohol measure was used to assess alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation